Thank you for the opportunity to help you with your question!
if you write this : 6h^-3/3h-9
6h^-3/3h-9 = 2h^-3/h-3 = (2/h^3)/(h - 3) = 2 / (h - 3)h^3
and if you write this : 6h^-3/3h^-9
6h^-3/3h^-9 = 2*3h^-3/3h^-9 = 2h^-3/h^-9 = (2/h^3)/(1/h^9) = 2h^9/h^3 = 2h^6
if you don't understand something just ask
Each time you have any other assignment or question just invite me i will give you the best answer
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?